Investigating Gender Differences on the Students’ Attitudes and Motivation toward English Learning - As Sabiq, Agus Husein; Arwi, Siti Hariroh; Khusna, Anisatul; Adifia, Dhelvy Ulfa Shita; Nada, Dhea Zabana Qothrun (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
Some researchers have researched to explore the effects of gender differences on learning outcomes. However, the interrelatedness of gender differences to attitudes and motivation needs to explore and investigate more. Thus, this study aimed to investigate the students' attitudes toward the English language and their motivation toward English language teaching based on gender differences in a state junior high school in Banyumas Regency, Central Java, Indonesia. There were 38 male and 32 female students who participated in this research. This research used a survey adapted from the Attitude/Motivation Test Battery (AMTB) and interviews in collecting the data. The researchers employed descriptive statistics and MANOVA for quantitative data and the Miles and Huberman model for qualitative data analysis. The findings showed a significant difference and effect of gender differences on the students' attitudes and motivation. Both male and female students revealed moderately high attitudes and motivation. However, female students showed a higher average score of the survey result. Less practice in real-life communication and limited exposure was the reason why the male students' have lower results in their attitudes and motivation toward English learning. Thus, providing authentic materials and exposure became some of the key points to improve meaningful learning experiences.